2015
DOI: 10.1186/s13660-015-0862-6
|View full text |Cite
|
Sign up to set email alerts
|

The Sugeno fuzzy integral of log-convex functions

Abstract: In this paper, we give an upper bound for the Sugeno fuzzy integral of log-convex functions using the classical Hadamard integral inequality. We present a geometric interpretation and some examples in the framework of the Lebesgue measure to illustrate the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…(1) If n i=1 g i = 1, then λ = 0; (2) If n i=1 g i < 1, then λ >0; (3) If n i=1 g i < 1, then − 1 ≤ λ > 0. There are many methods for calculating the fuzzy integral, such as Sugeno [20], Choquet [21], ordered weighted averaging AND operator (OWA-AND) [22], ordered weighted averaging OR operator (OWA-OR) [23], and Fuzzy min-max [24]. The Sugeno and Choquet methods were chosen in this study.…”
Section: The Proposed Efi-cnnsmentioning
confidence: 99%
“…(1) If n i=1 g i = 1, then λ = 0; (2) If n i=1 g i < 1, then λ >0; (3) If n i=1 g i < 1, then − 1 ≤ λ > 0. There are many methods for calculating the fuzzy integral, such as Sugeno [20], Choquet [21], ordered weighted averaging AND operator (OWA-AND) [22], ordered weighted averaging OR operator (OWA-OR) [23], and Fuzzy min-max [24]. The Sugeno and Choquet methods were chosen in this study.…”
Section: The Proposed Efi-cnnsmentioning
confidence: 99%
“…Recently, the integral inequalities for Sugeno integrals using different kinds of convexities and other results on several other types of inequalities based on Sugeno integrals are a thought-provoking topic to many authors in the field of fuzzy integrals, see for instance [20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the Hadamard inequality is a famous and important result, which provides the upper (lower) bound for the mean value of a log-convex (log-concave) function. Abbaszadeh et al [ 19 ] studied the Sugeno fuzzy integral of log-convex functions and showed that the Hadamard inequality is not valid for this kind of Sugeno fuzzy integral. Motivated by [ 19 ], we naturally wonder whether the Hadamard inequality still holds for the Choquet integral.…”
Section: Introductionmentioning
confidence: 99%
“…Abbaszadeh et al [ 19 ] studied the Sugeno fuzzy integral of log-convex functions and showed that the Hadamard inequality is not valid for this kind of Sugeno fuzzy integral. Motivated by [ 19 ], we naturally wonder whether the Hadamard inequality still holds for the Choquet integral. If the Hadamard inequality is not valid, then it is necessary to estimate the upper bound and the lower bound of the Choquet integral for log-convex functions.…”
Section: Introductionmentioning
confidence: 99%